IMPROVING STUDENT'S WEB USE AND INFORMATION LITERACY : A GUIDE FOR TEACHERS - Soleymani, Mohammad Reza, contributor 633863; Chawinga, Winner Dominic, contributor 633864; Duarte, Manuel Palomo, contributor 633865; Bulo, Inmaculada Medina, contributor 633866; Posada, Emilio Jose Rodriguez, contributor 633867; Lozano, Francisco Palomo, contributor 633868; Bralic, Antonia, contributor 633869; Divjak, Blazenka, contributor 633870; Osman, Hawa, contributor 633871; Furberg, Anniken, contributor 633872; Forte, Andrea, contributor 633873; Almarabeh, Tamara, contributor 633875; et al. (Hillingdon, United Kingdom : Koros Press Limited, 2019)
The web is now an integral part of students' lives in school and in society, and they need to be ever more web alert in order to gain the most from their education. What teachers and teacher librarians badly need to help them achieve this is a professional tool that combines knowledge and use of the web, Web 2.0 tools and information literacy for schools.This book fulfils that need by providing a practical guide to using the web effectively in order to enhance learning and teaching in schools. It does this by focusing on the knowledge and skills needed by teachers and teacher librarians to be information literate web users and to develop these abilities in their students. It then focuses on using Web 2.0 tools to create learning resources for students which will develop them as reflective web learners as well as web users. Key areas covered include:- learning and teaching in today's schools -- finding and using information on the web -- evaluating websites -- Web 2.0 and schools -- information literacy -- improving student use of the web -- developing learning websites for student use -- the next phase of ICT in schools.Set in a context of theory, this guide offers many examples of best practice in schools from a range of countries. Packed full with ideas which teachers and teacher librarians can use in their own schools, it is unique in providing a guide to the creation of learning websites, which combine subject learning, mediated resources for students, information literacy guidance (including effective web use), and student assignments.